Arrhythmic CArdiac DEath in MYotonic dystrophy type 1 patients (ACADEMY 1) study: the predictive role of programmed ventricular stimulation. Issue 7 (19th November 2021) - Russo, Vincenzo; Papa, Andrea Antonio; Rago, Anna; Ciardiello, Carmine; Martino, Anna Maria; Stazi, Alessandra; Golino, Paolo; Calò, Leonardo; Nigro, Gerardo
Abstract: Aims: Myotonic dystrophy type 1 (DM1) predisposes to the development of life-threatening arrhythmias and sudden cardiac death. Our study aimed to evaluate the prognostic value of programmed ventricular stimulation (PVS) in DM1 patients with conduction system disease. Methods and results: Arrhythmic CArdiac DEath in MYotonic dystrophy type 1 patients (ACADEMY 1) is a double-arm non-randomized interventional prospective study. Myotonic dystrophy type 1 patients with permanent cardiac pacing indication were eligible for the inclusion. The study population underwent to pacemaker (PM) or implantable cardioverter-defibrillator (ICD) implantation according to the inducibility of ventricular tachyarrhythmias at PVS. Primary endpoint of the study was a composite of appropriate ICD therapy and cardiac arrhythmic death. The secondary study endpoint was all-cause mortality. Seventy-two adult-onset DM1 patients (51 ± 12 years; 39 male) were enrolled in the study. A ventricular tachyarrhythmia was induced in 25 patients (34.7%) at PVS (PVS+) who underwent dual chambers ICD implantation. The remaining 47 patients (65.3%) without inducible ventricular tachyarrhythmia (PVS−) were treated with dual-chamber PM. During an average observation period of 44.7 ± 10.2 months, nine patients (12.5%) met the primary endpoint, four in the ICD group (16%) and five (10.6%) in the PM group. Thirteen patients died (18.5%), 2 in the ICD group (8%) and 11 in PM group (23.4%). The Kaplan–Meier analysis did not show a significantly different risk of both primary and secondary endpoint event rates between the two groups. Conclusions: The inducibility of ventricular tachyarrhythmias has shown a limited value in the arrhythmic risk stratification among DM1 patients.